(untitled) (Global Journal of Human-Social Science, 2023)
The newly discovered Hainan fisherman Zheng Changmei s copy of the South China Sea Liushui Genglubu is divided into two parts Liushui Record and Mountain Water Potential Map It is the only complete graphic-text combination of the South China Sea Genglubu found so far This book records the tide situation in the western sea area of Hainan Island the route around Hainan Island the route distance from Hainan Island to Guangdong province Guangxi province of China Vietnam and other places and 24 mountain water potential diagram The discovery of this book proves the use of Genglubu by merchant ships in Hainan Island the 24 sea charts are the continuation and development of the rare mountain shape and water potential maps in the literature of the past dynasties The drawing of the mountain shape and water potential has the characteristics of integrity which makes up for the rare sea charts in the Genglubu of the South China Sea In addition the record writing rules and drawing characteristics of the Six Collision Flow Methods in this book have the writing of Hainan Island dialect which has important reference value for the study of Hainan Fishermen s Island s navigation knowledge folk trade and local knowledge